Multilaboratory assessment of Epstein-Barr virus serologic assays: the case for standardization - Liu, Zhiwei; Waterboer, Tim (Journal of clinical microbiology, 2019)
IgA antibodies targeting Epstein-Barr virus (EBV) have been proposed for screening for nasopharyngeal carcinoma (NPC). However, methods differ, and the antigens used in these assays differ considerably between laboratories. To enable formal comparisons across a range of established EBV serology assays, we created a panel of 66 pooled serum samples and 66 pooled plasma samples generated from individuals with a broad range of IgA antibody levels. Aliquots from these panels were distributed to six laboratories and were tested by 26 assays measuring antibodies against VCA, EBNA1, EA-EBNA1, Zta, or EAd antigens. We estimated the correlation between assay pairs using Spearman coefficients (continuous measures) and percentages of agreement (positive versus negative, using predefined positivity cutoffs by each assay developer/manufacturer). While strong correlations were observed between some assays, considerable differences were also noted, even for assays that targeted the same protein. For VCA-IgA assays in serum, two distinct clusters were identified, with a median Spearman coefficient of 0.41 (range, 0.20 to 0.66) across these two clusters. EBNA1-IgA assays in serum grouped into a single cluster with a median Spearman coefficient of 0.79 (range, 0.71 to 0.89). Percentages of agreement differed broadly for both VCA-IgA (12% to 98%) and EBNA1-IgA (29% to 95%) assays in serum. Moderate-to-strong correlations were observed across assays in serum that targeted other proteins (correlations ranged from 0.44 to 0.76). Similar results were noted for plasma. We conclude that standardization of EBV serology assays is needed to allow for comparability of results obtained in different translational research studies across laboratories and populations.